Developing Critical Thinking Skills through Differentiated English Instruction in Philology Faculties (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Critical thinking is essential for academic success and professional development in philology, where analytical skills underpin language study and interpretation. This study examines the implementation of differentiated English instruction to foster critical thinking among students in philology faculties in Uzbekistan. Classroom observations, surveys, and interviews were analyzed to assess the effectiveness of tailored activities. Findings indicate significant improvements in analytical abilities, with differentiated strategies addressing diverse learner needs. Challenges include cultural norms favoring rote learning, but incremental integration proved beneficial. Results underscore the potential of differentiated approaches to enhance critical thinking in EFL contexts within Uzbekistan's higher education system.